التسويق الإلكتروني وتطبيقات الذكاء الإصطناعي - بن لوصيف, حنان; بولحية, سليم (جامعة الوادي - University of Eloued, 2023)
يعد كل من الذكاء الإصطناعي والتسويق الإلكتروني علوما حديثة ولذلك يسعى العديد من الباحثين وخبراء التسويق لخلق توليفة رقمية متكاملة بينهما ،فالذكاء الإصطناعي أصبح بمثابة المحرك الرئيسي في ترسانة المسوقين الرقميين نتيجة إحداثه ثورة غير مسبوقة في صناعة التسويق وأصبحت كل المنشآت بحاجة إليه لضمان الوصول إلى المستهلك الرقمي. وعليه تهدف هذه الورقة البحثية إلى تحديد العلاقة أوطبيعة الإرتباط الوثيق بينهما وكذلك معرفة أهم التقنيات والإبتكارات التكنولوجية التي يتم توظيفها لتحقيق مختلف الأهداف التسويقية ولقد إرتأينا في هذه الدراسة الإعتماد على المنهج الوصفي التحليلي لأنه الأنسب لتوصيفها. وقد تم التوصل إلى أن الذكاء الإصطناعي هو ميزة إستراتيجية حتمية في مجال التسويق كونه يعمل على الحصول على كفاءة أكبر ويقدم فرص جديدة لتعزيز ولاء العملاء، كما أنه تحول بسرعة إلى ميزة تنافسية للعديد من المؤسسات. وكذلك للحفاظ على القدرة التنافسية التسويقية يجب على كل مؤسسة إحتضان الذكاء الإصطناعي وإنشاء نظام بيئي له خاصة وأن هذا الأخير أثبت أنه أداة ثورية في كل صناعة. Abstract: Both artificial intelligence and e -marketing are modern science and therefore many researchers and marketing experts seek to create an integrated digital combination between them, as artificial intelligence has become the main driver in the arsenal of digital marketers as a result of its creation of an unprecedented revolution in the marketing industry and all facilities need it to ensure access to the digital consumer . Accordingly, this research paper aims to determine the relationship or the character of the close connection between them, as well as knowing the most important technologies and technological innovations that are employed to achieve various marketing goals. In this study, we decided to rely on the descriptive analytical approach because it is the most appropriate to its description. It has been concluded that artificial intelligence is an inevitable strategic advantage in the field of marketing, as it works to obtain greater efficiency and provides new opportunities to enhance customer loyalty, and has quickly turned into a competitive advantage for many institutions. Likewise, to preserve the marketing competitiveness, each institution must embrace artificial intelligence and create an ecosystem for it, especially since the latter has proven to be a revolutionary tool in every industry
العلاقة الإرتباطية في ظل التحولات الرقمية
مقال
Keywords: التسويق الإلكتروني ; الذكاء الإصطناعي ; البلوكتشين ; التعلم الآلي ; الخوارزميات; e -marketing, artificial intelligence, blockchain, machine learning, algorithms.